2023
DOI: 10.3389/fphar.2023.1199152
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the stimulator of interferon genes (STING) in breast cancer

Abstract: Breast cancer has a high occurrence rate globally and its treatment has demonstrated clinical efficacy with the use of systemic chemotherapy and immune checkpoint blockade. Insufficient cytotoxic T lymphocyte infiltration and the accumulation of immunosuppressive cells within tumours are the primary factors responsible for the inadequate clinical effectiveness of breast cancer treatment. The stimulator of interferon genes (STING) represents a pivotal protein in the innate immune response. Upon activation, STIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…However, this small-scaled exploratory study has indicated that activated intra-tumor immune microenvironments may play an important role in pathological responses to NAC, and that the up-regulation of vimentin and v+ in the residual tumors may be pivotal prognostic factors in non-pCR cases to NAC. Enhancement of intra-tumor immunity before the NAC introduction using pre-operative radiotherapy or immunepotentiating agents might provide a greater anti-tumor activity of NAC [27][28][29]. Additionally, anti-EMT agents together with NAC might improve the outcome of patients with TNBCs [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, this small-scaled exploratory study has indicated that activated intra-tumor immune microenvironments may play an important role in pathological responses to NAC, and that the up-regulation of vimentin and v+ in the residual tumors may be pivotal prognostic factors in non-pCR cases to NAC. Enhancement of intra-tumor immunity before the NAC introduction using pre-operative radiotherapy or immunepotentiating agents might provide a greater anti-tumor activity of NAC [27][28][29]. Additionally, anti-EMT agents together with NAC might improve the outcome of patients with TNBCs [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Both innate and adaptive immune cells play a role in these antithetical responses. Altered DNA damage responses (DDRs) following constitutional mutations of the genes involved in the HRR pathway or exposure to cytotoxic agents cause activation of the inflammatory STING (stimulating interferon gene) pathway leading to anti-tumor response (Figure 4) [90]. The soluble DNA released from defective DDR will cause an enzymatic activation of cyclic guanosine monophosphate-adenosine monophosphate synthetase (cGAS) leading to the synthesis of the second messenger, 2 ′ 3 ′ -Cyclic GMP-AMP (cGAMP) [91].…”
Section: Impact Of Brcaness On Tumor Immunitymentioning
confidence: 99%